2011
DOI: 10.1007/s00213-011-2341-1
|View full text |Cite
|
Sign up to set email alerts
|

Systematic review of the relationship between the 3-hydroxycotinine/cotinine ratio and cigarette dependence

Abstract: The evidence that the ratio is related to smoking behaviours and to cigarette dependence is limited, but the ratio seems to influence treatment response to two stop smoking medications. Further studies of the relationship between the ratio and cigarette dependence and trials of ratio-guided pharmacotherapy are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 35 publications
(115 reference statements)
4
53
1
Order By: Relevance
“…Greater NMR was associated with a faster increase in anxiety but a slower increase in craving during early withdrawal. Greater NMR also was related to greater cigarette consumption and more severe withdrawal symptoms at follow-up assessments, which is consistent with prior research (West et al, 2011). Thus, the effect of the rate of nicotine metabolism on smoking cessation outcomes may be mediated by its impact on the rates of change of anxiety and craving during early withdrawal.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…Greater NMR was associated with a faster increase in anxiety but a slower increase in craving during early withdrawal. Greater NMR also was related to greater cigarette consumption and more severe withdrawal symptoms at follow-up assessments, which is consistent with prior research (West et al, 2011). Thus, the effect of the rate of nicotine metabolism on smoking cessation outcomes may be mediated by its impact on the rates of change of anxiety and craving during early withdrawal.…”
Section: Resultssupporting
confidence: 84%
“…Greater ratios indicate faster clearance (St. Helen, Jacob, & Benowitz, 2013) and might be expected to associate with more prominent withdrawal symptoms. One study found that greater NMR is associated with greater craving 1 week postquit (Lerman et al, 2006), but this finding failed to replicate (West, Hajek, & McRobbie, 2011). In a study of adolescent light smokers, greater NMR was associated with more severe withdrawal symptoms following 24 hr of supervised abstinence (Rubinstein, Benowitz, Auerback, & Moscicki, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The clinical correlations of the NMR have been examined in several studies (Malaiyandi et al, 2006). Although the NMR did not consistently correlate with nicotine dependence or cigarette consumption (for a review see (West et al, 2011)), it did correlate with withdrawal severity in adolescent smokers (Rubinstein et al, 2008) and higher craving in smokers using nicotine patch . A recent study suggested that the NMR might influence smoking behavior; smokers with higher NMR had greater puff volumes and increased levels of carcinogen biomarker (Strasser et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The role of nicotine metabolites and corresponding metabolic ratios in various matrices, including oral fluid, as biomarkers of exposure to tobacco smoke, smoking cessation or to guide treatment of nicotine dependence has been thoroughly explored, as indicated in several studies and recent review papers [105][106][107][108][109][110]. Here, we will discuss studies that specifically evaluated the usefulness of nicotine metabolic ratios in oral fluid for CYP2A6 phenotyping.…”
Section: Oral Fluidmentioning
confidence: 99%